Efficacy and safety of CT-guided 125I seed implantation by coplanar template as a salvage therapy for vertebral metastases after failure of external beam radiation therapy: a retrospective study - Li, Peishun; Bai, Yunling; Yuan, Qianqian; Man, Qirong; Xing, Chao; Ren, Yanchen; Zhang, Kaixian (Frontiers in Oncology, 2023)
Purpose To evaluate the efficacy safety of computed tomography (CT)-guided 125I seed implantation by coplanar template for vertebral metastases after failure of external beam radiation therapy (EBRT). Material and methods Retrospective analysis of the clinical outcomes of 58 patients with vertebral metastases after failure of EBRT, who underwent 125I seed implantation as a salvage treatment with a CT-guided coplanar template-assisted technique from January 2015 to January 2017. Results The mean post-operative NRS score decreased significantly at T4w (3.5 ± 0.9, p<0.01), T8w (2.1 ± 0.9, p<0.01), T12w (1.5 ± 0.7, p< 0.01) and T6m (1.2 ± 0.6, p< 0.01) respectively. The local control rates after 3, 6, 9 and 12 months were 100% (58/58), 93.1% (54/58), 87.9% (51/58), and 81% (47/58), respectively. The median overall survival time was 18.52months (95% CI, 16.24-20.8), and 1- and 2-year survival rates were 81% (47/58) and 34.5% (20/58), respectively. By performing a paired t-test analysis, there was no significant difference in D90, V90, D100, V100, V150, V200, GTV volume, CI, EI and HI between preoperative and postoperative (p>0.05). Conclusions 125I seed implantation can be used as a salvage treatment for patients with vertebral metastases after failure of EBRT.